Treatment of advanced gastrointestinal cancer with genetically modified autologous mesenchymal stem cells: Results from the phase 1/2 TREAT‐ME‐1 trial. Issue 6 (13th March 2019) - von Einem, Jobst Christian; Guenther, Christine; Volk, Hans‐Dieter; Grütz, Gerald; Hirsch, Daniela; Salat, Christoph; Stoetzer, Oliver; Nelson, Peter J.; Michl, Marlies; Modest, Dominik P.; Holch, Julian W.; Angele, Martin; et al.
Abstract : TREAT‐ME‐1, a Phase 1/2 open‐label multicenter, first‐in‐human, first‐in‐class trial, evaluated the safety, tolerability and efficacy of treatment with genetically modified autologous mesenchymal stromal cells (MSC), MSC_ apceth_101, in combination with ganciclovir in patients with advanced gastrointestinal adenocarcinoma. Immunological and inflammatory markers were also assessed. All patients (3 in Phase 1; 7 in Phase 2) received three treatment cycles of MSC_apceth_101 at one dose level on Day 0, 7, and 14 followed by ganciclovir administration according to the manufacturer's instructions for 48─72 h after MSC_apceth_101 injection. Ten patients were treated with a total dose of 3.0 x 10 6 cells/kg MSC_apceth_101. 36 adverse events and six serious adverse events were reported. Five patients achieved stable disease (change in target lesions of −2 to +28%). For all patients, the median time to progression was 1.8 months (95% CI: 0.5, 3.9 months). Median overall survival could not be estimated as 8/10 patients were still alive at the end of the study (1 year) and therefore censored. Post‐study observation of patients showed a median overall survival of 15.6 months (ranging from 2.2─27.0 months). Treatment with MSC_apceth_101 and ganciclovir did not induce a consistent increase or decrease in levels of any of the tumor markers analyzed. No clear trends in the immunological markers assessed were observed. MSC_apceth_101 in combination with ganciclovir was safe and tolerable in patients with advanced gastrointestinal adenocarcinoma, with preliminary signs of efficacy in terms of clinical stabilization of disease. Abstract : What's new? The first clinical trial of human autologous genetically engineered mesenchymal stem cells (MSCs) for solid tumor treatment appears successful. MSCs have been an attractive vehicle for delivering tumor‐killing factors because many cancers recruit them to the tumor site for a growth boost. Here, the authors tested cells called MSC_apceth_101, which are engineered to selectively express herpes simplex virus tyrosine kinase (HSV‐TK) when they reach the tumor site. HSV‐TK phosphorylates ganciclovir, generating a toxic metabolite. In this phase I/II clinical trial, the authors showed that MSC_apceth_101 cells combined with ganciclovir was safe and tolerated by patients with advanced gastrointestinal adenocarcinoma.